ON THE ASSESSMENT OF THE FLIGHT OPERATIONS MANAGEMENT SYSTEM’S EFFICIENCY IN INCOMPLETE INFORMATION CONDITIONS - Bondik , Oleksandr; Zarubinska, Iryna; Kosohov, Oleksandr (Science-based technologies, 2025)
The new requirements of modern management systems in our highly technological flight opera-tions demand that critical systems be adaptable, especially in incomplete information conditions. This work focuses on the FOMS adaptation and presents a set of comprehensive techniques to be used in the development of FOMSs to increase their level of adaptation during incomplete information conditions in flight operations. That’s why the assessing the Flight Operations Management System’s efficiency under incomplete information requires considering the role of uncertainty, data gaps, and real-time decision-making. The purpose of this article is to present a new assessment approach of the Airlines Flight Operations Management System’s (FOMS) functioning efficiency in incomplete information conditions. Methods: The article describes the runtime method which increase the adaptation degree of Airlines FOMS to functioning in incomplete information conditions, such as the assessing method of management quality influence on the managed system’s performance with a specific metric called FOMS’s Effectiveness EFMOS to evaluate this influence by varying influence factors related to the management system within it’s management strategy. Results: An analytical model of management quality influence on the Airlines FOMS’s effectiveness. Discussion: The proposed new approach will allow to increase the Airlines FOMS’s functioning efficiency in a high degree of uncertainty and incomplete information conditions. Future research will explore scenarios where management activities, such as load balancing and admission control, could enhance and sustain the FOMS’s performance and efficiency.